The effect of binaural noise and sensitivity on brain-stem evoked response - Vijayashree (Journal of All India Institute of Speech and Hearing)
The present study was aimed at investigating whether there is any effect of binaural noise on the latency and amplitude of brain-stem response. The study was also aimed at finding out the effect on latency and amplitude of brain-stem response at different values of sensitivity.